2021
DOI: 10.36941/mjss-2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Increase Enrolment: Its effect on teachers in Ghana

Abstract: This study investigated the effects of increase in enrolment on teachers in second cycle institutions in Ghana. The effects of increase enrolment on teacher’s work load, classroom management, health, social life and classroom interaction. The study employed the pragmatic paradigm and mixed method approach. Concurrent triangulation comprising descriptive survey for the quantitative phase and a case study for the qualitative phase.  Self-developed questionnaire and semi-structured interview schedule were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The last six years' trends for secondary teachers and schools have also been tested to determine gender parity and gathered that only 5% had been female instructors against 30% sub-Saharan Africa benchmark (UNESCO, 2021), while, on average, the proportion of secondary students to qualified, or certified teachers are characteristically between 40 -43:1 respectively (Ndethiu et al, 2017;Catherine, 2011;Akoto-Baako, 2021). Despite the fact that the distribution of teachers varies widely among the various countries, this is consistent with the tradeoff between teacher salary and student-teacher ratio across the majority of sub-Saharan African countries.…”
Section: Discussionmentioning
confidence: 99%
“…The last six years' trends for secondary teachers and schools have also been tested to determine gender parity and gathered that only 5% had been female instructors against 30% sub-Saharan Africa benchmark (UNESCO, 2021), while, on average, the proportion of secondary students to qualified, or certified teachers are characteristically between 40 -43:1 respectively (Ndethiu et al, 2017;Catherine, 2011;Akoto-Baako, 2021). Despite the fact that the distribution of teachers varies widely among the various countries, this is consistent with the tradeoff between teacher salary and student-teacher ratio across the majority of sub-Saharan African countries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significance of teachers in shaping the future of Ghana, their profession is fraught with multifaceted challenges that contribute to burnout. Teachers often grapple with heavy workloads, demanding administrative responsibilities, limited resources, and overcrowded classrooms [10,11]. Also, Sam et al [12] revealed that conventional teaching can lead to a higher incidence of employee burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of teachers in shaping the future of Ghana, their profession is fraught with multifaceted challenges that contribute to burnout. Teachers often grapple with heavy workloads, demanding administrative responsibilities, limited resources, and overcrowded classrooms [10,11]. Also, Sam et al [12] revealed that conventional teaching can lead to a higher incidence of employee burnout.…”
Section: Introductionmentioning
confidence: 99%